Automated knowledge extraction from Internet for a crisis communication portal - Goh, Ong Sing; Fung, C.C. (Springer Berlin, 2005)
This paper describes the development of an Automated Knowledge Extraction Agent (AKEA) which was designed to acquire online news and document from the internet for the establishment of a knowledge based crisis communication portal. It was recognized that in times of crisis, an effective communication mechanism is essential to maintain peace and calmness in the community by providing timely and appropriate information. It is proposed that the incorporation of software agents into the crisis communication portal will be capable to send alert news to subscribed users via internet and mobile services. The proposed system consists of crawler, wrapper, name-entity tagger, AIML (Artificial Intelligence Markup language) and an animated character is used in the front-end for human computer communication.